Review Essay: Working evangelicalisms: Deploying fragmented theologies in secular space - TSE, Justin Kh (Institutional Knowledge at Singapore Management University, 2013)
Over the last three years, three new important books have contributed to critical geographies of American evangelicalism: Jason Dittmer and Tristan Sturm’s Mapping the End Times, Jason Hackworth’s Faith Based, and Justin G. Wilford’s Sacred Subdivisions. Demonstrating that evangelicals are ignored at geographers’ peril in political, economic, and cultural geography, these new books each demonstrate that evangelical usages of space have contemporary salience in secular geopolitical formations, domestic economic policy, and the interpretation of cultural landscapes. Because these three books represent three different subfields in human geography (political, economic, and cultural geography), they can be taken together to critically interrogate the ways in which evangelicals use their theologies to exert secular power on a variety of modern spatial constructions. The strengths of each of these books are thus also their weakness, for although their critiques rightly interrogate the secular ends of some evangelical practices, the varieties of evangelical theologies are seldom explored, particularly in how contestations over the word evangelical shape the ways in which self-identifying evangelicals have made places.